2014
DOI: 10.3109/03008207.2014.923875
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase expression in keratocystic odontogenic tumors and primary cells

Abstract: KCOT primary cell populations and tumors express a wide range of MMPs, which likely play a role in the bone-invasive nature of these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…They are thought to play a role in the locally invasive nature of odontogenic tumors. Many studies have shown the expression of various MMPs in odontogenic tumors, including ameloblastomas and KCOT [48, 51, 5557]. Treating AME-HPV cells with EGF induced increased expression of MMP-2 and MMP-9, and increased the rates of invasion and migration of these cells [54].…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…They are thought to play a role in the locally invasive nature of odontogenic tumors. Many studies have shown the expression of various MMPs in odontogenic tumors, including ameloblastomas and KCOT [48, 51, 5557]. Treating AME-HPV cells with EGF induced increased expression of MMP-2 and MMP-9, and increased the rates of invasion and migration of these cells [54].…”
Section: Epidermal Growth Factor Receptor (Egfr)mentioning
confidence: 99%
“…38,39 MMPs have been detected in both cyst fluids and wall tissue extracts of various odontogenic cysts and odontogenic tumors, including ABs, suggesting that these enzymes play a key role in regulation of tumor and cyst growth. [40][41][42][43] In the present research, the expression of MMP in AB and its effect on tumor cell invasion and the prognosis of patients were varied. Thus, identification of prognostic values of the MMPs in ABs is of considerable importance to determine the most appropriate therapeutic approach and establish the prognosis of patient.…”
Section: Discussionmentioning
confidence: 83%
“…Because MMP2 and MMP-9 can degrade bone matrix and in turn release mitogenic factors to enhance tumor cell proliferation, MMP2 and MMP-9 may play an important role in the local invasiveness of ameloblastomas (10). For KCOTs, the MMP-2 expression is found in all examined samples and in the basal cells and basement membrane zone of the detached lining epithelium (11). Furthermore, the active form of MMP-9 is frequently detected in KCOTs (12).…”
Section: Discussionmentioning
confidence: 95%